Realities of economic livelihood strategies of urban poor Malay families during Covid-19 pandemic / Nor Hafizah Mohamed Harith and Nur Fatima Aisya Jamil - Mohamed Harith, Nor Hafizah; Jamil, Nur Fatima Aisya (2021)
Rakodi and Llyod-Jones (2002) explain that vulnerability is a threat to the urban poor. It includes the ability of the poor to recover or be resilient to overcome shocks, stresses, and longterm socio-economic life difficulties. However, Moser (1996) argues that the ability to avoid or reduce vulnerability depends on the capacity of the poor to manage and transform these assets into income, food, or other necessities to sustain their livelihood. Nevertheless, the outbreak of COVID-19 poses a significant threat and economic vulnerability for the urban poor in sustaining their livelihood. The first case of COVID-19 was brought into Malaysia by Chinese nationals in February 2020. As of 24 September 2021, Malaysia reported more than 2 million COVID-19 cases (Ministry of Health Malaysia, 2021). The economic catastrophe of the COVID-19 is tremendous. The latest Gini Coefficient score released by the Department of Statistics, Malaysia (2020) measures income and wealth inequality within a country, increased by 0.008 index points from 0.399 in 2016 to 0.407 in 2019, indicating the income gap between households is widening. As of today, the COVID-19 and movement restriction had adversely affected the poor urban. The socio-economic factors of approximately half of the low-income households living in the capital city's public flats worsened further in the fourth quarter of 2020 (UNICEF & UNFPA, 2020).